Student companion to Arthur Miller - Abbotson, Susan C. W., 1961- (Student companions to classic writers., 2000)
Examines Arthur Miller's life, his literary heritage, and eight works from "All my Sons" to "The Ride Down Mt. Morgan," discusses literary style, points of view, and setting, and offers analyses from different critical approaches.